Policy Strategies in the Implementation of Referral Health Service Transformation - Rahmawati, Elfi (Jurnal Multidisiplin Indonesia, 2024)
The implementation of the transformation of referral healthcare services aims to improve access and quality of healthcare services in Indonesia; however, its execution has not been optimal. This is due to the hospital ecosystem not yet supporting service development, and hospitals' responses that are not quick and accurate in addressing changes in disease patterns and public demands. This policy document is prepared to bridge the implementation of healthcare service transformation at the Ministry of Health, which has been developed by the Ministry of Health into focused operational strategies and policies to ensure the realization of referral healthcare service transformation. These strategies and policies are developed through an in-depth review of data on referral healthcare services and the condition of healthcare services in Indonesia, as well as the existing planning and budgeting policies. Furthermore, the analysis used in formulating the strategies and policies includes problem tree analysis and Bardach's Evaluation Technique. The formulated policy concerns the adjustment of the Ministry of Health's Planning and Budgeting Policy as stated in the Minister of Health Regulation No. 48 of 2017 on Guidelines for Health Planning and Budgeting by adding the following substance the referral healthcare service program as one of the foundations for establishing planning and budgeting policies at the Ministry of Health,  Prioritizing the budget for the implementation of referral healthcare transformation through tagging the referral healthcare transformation program in the Krisna application, Rules regarding the planning and budgeting patterns of BLU work units, which have specific management characteristics, including the use of initial balances and the establishment of expenditure thresholds.